The political economy of growing a rural university in the United States using online education: an examination of incentives for educational imperialism and academic capitalism - Zacharakis, Jeffrey T.; Tolar, Mary H.; Collins, Royce A. (My University, 2014)
Rural colleges and universities in the USA struggle to recruit new students as their geographic region is depopulating and cost to attend classes on campus are increasing. Online education using the Internet is rapidly expanding as an effective growth strategy to reach new groups of students. In this paper we take the position that online education is a form of cultural imperialism and academic capitalism where curriculum developers and professors are motivated to enroll new students in order to maintain the credibility and strength of their programmes and host institutions. We argue that it is not our intent to be educational imperialists or capitalists. Rather these are unintended consequences of our actions. This argument is supported by political economy theory in that we are marketing a technical rational form of online education without awareness of its long‐term cultural, economic, or political ramifications. Even though we pride ourselves on developing a high quality programme that in our eyes meet the needs of our students, understanding the political economy of online education is essential if our programme that has access to the global market is to go beyond the individual needs of students and address social, cultural and political needs. We conclude that one way out of this malaise is to understand our role as instructors and course designers as a first step toward understanding the intended and unintended consequences of online education.
The political economy of growing a rural university in the USA using online education: An examination of incentives for educational imperialism and academic capitalism
Keywords: Online education; University recruitment; Cultural imperialism; Academic capitalism; Rural university